Lyapunov Characterization for the Stability of Stochastic Control Systems. (23rd February 2015) - Abedi, Fakhreddin; Leong, Wah June; Abedi, Mohammad
Abstract : Lyapunov-like characterization for the problem of input-to-state stability in the probability of nonautonomous stochastic control systems is established. We extend the well-known Artstein-Sontag theorem to derive the necessary and sufficient conditions for the input-to-state stabilization of stochastic control systems. Illustrating example is provided.